Prevalence, awareness, and associated factors of airflow obstruction in russia: the Ural eye and medical study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Zainullin, Rinat M.; Salavatova, Venera F.; Arslangareeva, Inga I.; Panda-Jonas, Songhomitra; Gilmanshin, Timur R.; Nikitin, Nikolai A.; Mukhamadieva, Svetlana R.; Yakupova, Dilya F.; Khikmatullin, Renat I.; Aminev, Said K.; et al. (Frontiers in Public Health, 2019)
Background: Although chronic obstructive pulmonary disease and asthma belong to the most important causes of disability and death in all world regions, data about the prevalence of airflow obstruction and asthma in Russia and the associated parameters have been scarce so far. We therefore assessed the prevalence of airflow obstruction and asthma in a Russian population. Methods: The population-based Ural Eye and Medical Study, conducted in a rural and urban region of Bashkortostan/Russia, included 5392 participants (mean age:58.6±10.6 years;range:40-94 years) out of 7328 eligible individuals. Airflow obstruction was defined spirometrically and asthma by self-reported diagnosis. Results: Airflow obstruction was present in 369 individuals (6.8%;95% confidence interval (CI):6.2,7.5) with an awareness rate of 63.4% (95%CI:58.5,68.4) and known duration of 19.5±15.8 years (median:16 years). Prevalence of undiagnosed airflow obstruction was 2.6% (95%CI:2.2,3.1). Higher prevalence of airflow obstruction was associated (multivariable analysis) with higher prevalence of current smoking (P<0.001;odds ratio (OR):2.91;95%CI:1.76,4.83) and number of cigarette package years (P<0.001;OR:1.03;95%CI:1.02,1.08), female gender (P=0.03;OR:1.42;95%CI:1.04,1.93), urban region (P=0.003;OR:1.43;95%CI:1.12,1.79), higher prevalence cardiovascular diseases/stroke (P<0.001;OR:1.86;95%CI:1.45,2.39), higher depression score (P=0.002;OR:1.05;95%CI:1.02,1.08), and lower physical activity (P=0.01;OR:0.71;95%VI:0.54,0.93). Asthma prevalence (2.6%;95%CI:2.0,3.1;known duration:17.2±15.0 years) was associated with less alcohol consumption (OR:0.53;95%CI:0.33,0.87;P=0.01), higher depression score (OR:1.08;95%CI:1.03,1.12;P<0.001), and urban region (OR:0.68;95CI:0.49,0.95;P=0.0.03). Conclusions: In this Russian population aged 40+ years, the prevalence of airflow obstruction was 6.8% with an awareness rate of 63.4% and smoking as main risk factor. Asthma prevalence was 2.6%.
Gesehen am 13.01.2020